Dimensions of food - Vaclavick, Vickie A.; Devine, Marjorie M.; Pimentel, Marcia H. (CRC Press, 2010)
Includes the January 2005 American Dietary Guidelines as well as the US Department of Agriculture food pyramid. This text helps build an understanding of the functional and structural properties of the components of foods